Production process of sodium ion battery

By using asphalt and starch mixed material and graphene oxide as the negative electrode material of sodium ion battery and combined with appropriate binders and process treatment, the poor conductivity and volume expansion problems of the existing sodium ion battery negative electrode materials are solved, and the electrochemical performance and cycle life of the battery are improved.

CN119695074APending Publication Date: 2025-03-25CHINA SODA ENERGY (YANGZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411880165.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing negative electrode materials of sodium ion batteries have the disadvantages of high charging voltage platform, poor conductivity, and serious volume expansion, resulting in low first-time Coulomb efficiency, poor rate performance, short cycle life and low energy density of sodium ion batteries.

Method used

The negative electrode sheet is prepared by mixing and matching as the active material for the negative electrode of the sodium ion battery, and after the carbonization treatment, graphene oxide and appropriate binder are added, and the negative electrode sheet is prepared by spray freeze-drying and spin coating.

Benefits of technology

It improves the output power and charge and discharge efficiency of sodium ion batteries, reduces the production cost of negative electrode materials, extends the battery's cycle life, and enhances electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198007480000101
    Figure BDA0005198007480000101
  • Figure BDA0005198007480000111
    Figure BDA0005198007480000111
Patent Text Reader

Abstract

The invention discloses a production process of a sodium ion battery. The production process comprises the following steps: assembling a positive plate, a negative plate, a diaphragm and an electrolyte to obtain the sodium-ion battery, and a preparation method of the negative plate specifically comprises the following steps: a, dispersing graphene oxide in water, then adding starch, stirring for 2.5-3.0 hours at the temperature of 80-85 DEG C, then cooling to 35-40 DEG C, and then cooling to room temperature; then adding asphalt dispersed in absolute ethyl alcohol, and mixing and stirring for 20-30 minutes to obtain a mixed solution; carrying out spray freeze drying on the mixed solution, and then carrying out carbonization treatment under the protection of inert gas to obtain an active material; and b, uniformly mixing an active material, a conductive agent and a binder, then dispersing the mixture in a solvent, magnetically stirring the mixture uniformly, then coating the mixture on a metal aluminum foil, and then drying and tabletting the mixture to obtain the negative plate. The sodium ion battery prepared by the production process provided by the invention has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of preparing sodium ion batteries, and more specifically, it relates to a production process for sodium ion batteries. Background Art

[0002] With the increase in energy demand, the depletion of fossil fuel reserves and the increasing prominence of environmental issues, renewable clean energy such as wind energy, solar energy and nuclear energy has been widely studied. However, to achieve the successful application of renewable energy technology, it is necessary to develop efficient, cost-effective and large-scale energy storage systems. Lithium-ion batteries are currently the most widely used energy storage device. Since they were commercialized by Sony in the 1990s, they have been widely used in modern life. However, the limited lithium resources and the cost of lithium metal battery components have restricted the large-scale development of lithium-ion batteries.

[0003] Sodium is the fourth most abundant metal element in the earth's crust and has similar chemical properties to lithium. Therefore, sodium-ion batteries have attracted extensive research and may replace lithium-ion batteries as the ultimate application direction of secondary batteries in the future. Among them, the negative electrode material is the core component that determines the performance of sodium-ion batteries and plays a key role in affecting key performance indicators such as energy density, power density, cycle life and safety. At present, many researchers have developed various high-specific-capacity embedded sodium-ion battery negative electrode materials, such as transition metal oxides, sulfides, selenides, etc. However, these negative electrode materials all have disadvantages such as high charging voltage platform, poor conductivity, and severe volume expansion, which leads to low first coulombic efficiency, poor rate performance, short cycle life and low energy density in sodium-ion batteries.

[0004] In comparison, hard carbon materials have the advantages of low raw material cost, simple preparation, high sodium storage capacity, low charging voltage platform, and small volume expansion rate, and are regarded as ideal negative electrode materials for sodium ion batteries. Unlike traditional graphite, hard carbon materials are composed of short-range disordered graphite-like domain structures, and have abundant closed-pore structures and larger graphite layer spacing (>0.37nm). These microstructures are conducive to accelerating the storage reaction and transmission rate of sodium ions during the charging and discharging process. Currently, common hard carbon material precursors include biomass, resins, sugars, high molecular polymers, etc. However, these raw materials have problems such as high price, poor consistency, low carbon yield, and complex processing technology, which greatly increases the preparation cost of hard carbon negative electrode materials for sodium ion batteries, which is not conducive to their commercial application. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a production process of a sodium ion battery.

[0006] The present application provides a sodium ion battery production process, which adopts the following technical solution: A production process for a sodium ion battery comprises the following steps: assembling a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte to obtain a sodium ion battery, wherein the preparation method of the negative electrode sheet is specifically as follows: a. Dispersing graphene oxide in water, then adding starch and stirring at a temperature of 80-85° C. for 2.5-3.0 hours, the weight ratio of starch to graphene oxide is (12-16):1, then cooling to 35-40° C., adding asphalt dispersed in anhydrous ethanol and stirring for 20-30 minutes to obtain a mixed solution, the weight ratio of asphalt to starch is (2.5-3.5):1; spray freeze drying the mixed solution, and then carbonizing it under the protection of an inert gas to obtain an active material; b. The active material, conductive agent and binder in a weight ratio of (75-85):(5-15):(5-15) are mixed evenly, then dispersed in a solvent, magnetically stirred evenly and coated on a metal aluminum foil, and then dried and pressed to obtain a negative electrode sheet.

[0007] By adopting the above technical scheme, the present application mixes asphalt and starch which have the characteristics of high carbon yield, low ash content, low cost and simple processing technology and uses them as the active material of the negative electrode of the sodium ion battery. It can not only give full play to the synergistic effect between the two, so that the sodium ion battery has higher output power and charge and discharge efficiency, but also reduce the preparation cost of the negative electrode material, and broaden the development space of the sodium ion battery.

[0008] The addition of asphalt can also form a protective film on the surface of the negative electrode material, reducing the direct contact between the negative electrode material and the electrolyte, thereby reducing the reaction rate of the side reaction, which not only helps to slow down the degradation rate of the negative electrode material, but also reduces the capacity loss of the sodium ion battery during the charge and discharge process, and prolongs the cycle life of the sodium ion battery. In addition, asphalt also has good stability and sealing properties, can effectively fill the gaps between starch carbon particles, enhance the structural stability of the negative electrode material, help resist the volume change produced by the sodium ion battery during the charge and discharge process, and reduce the possibility of fatigue and damage to the negative electrode material.

[0009] At the same time, the present application also adds a small amount of graphene oxide to the negative electrode material, and uses graphene oxide to effectively induce the graphitization of starch and asphalt, thereby improving the conductivity and structural stability of the negative electrode material and promoting the transmission of sodium ions, thereby improving the charge and discharge performance, rate performance and cycle stability of the sodium ion battery.

[0010] Preferably, the starch in step a is amylopectin.

[0011] By adopting the above technical scheme, the present application adopts branched-chain starch as one of the raw materials of the negative electrode material, which can further improve the charge and discharge performance, rate performance and cycle stability of the sodium ion battery compared with corn starch (branched content of 80%) and high branched-chain starch (branched content of 40%).

[0012] Preferably, the asphalt in step a is sulfided asphalt.

[0013] Preferably, the sulfided asphalt is prepared by the following method: Asphalt and sublimed sulfur in a weight ratio of 1:(1.8-2.2) are uniformly mixed, and then treated at a temperature of 250-300° C. for 2.5-3.0 hours under the protection of an inert gas to obtain sulfided asphalt.

[0014] Through the above technical scheme, compared with ordinary asphalt, the present application uses asphalt doped with sulfur, which can utilize the doping of sulfur to expand the interlayer spacing of the material, significantly reduce the diffusion barrier of sodium ions, and increase the diffusion rate of sodium ions, thereby increasing the diffusion coefficient of sodium ions and further improving the electrochemical performance of sodium ion batteries.

[0015] Preferably, the carbonization treatment conditions in step a are: at a temperature of 950-1050° C. for 2.5-3.5 hours.

[0016] Preferably, the binder in step b is one of sodium alginate, sodium polyacrylate and carboxymethyl cellulose binders.

[0017] Through the above technical scheme, the present application adopts one of sodium alginate, sodium polyacrylate and carboxymethyl cellulose binder (the weight ratio of carboxymethyl cellulose and styrene-butadiene rubber is 1:1) as a binder. Compared with traditional polyvinylidene fluoride, it can be more evenly dispersed on the surface of the active material without agglomeration, thereby constructing a passivation film between the electrolyte and the active material, inhibiting the excessive generation of SEI film in the electrochemical reaction, reducing the consumption of sodium ions, and improving the first coulombic efficiency of the sodium ion battery.

[0018] Preferably, the binder in step b comprises sodium alginate and sodium polyacrylate in a weight ratio of (0.8-1.2):1.

[0019] Through the above technical scheme, the present application adopts a mixture of sodium alginate and sodium polyacrylate as a binder, which can give full play to the synergistic effect between the two binders, thereby further inhibiting the excessive generation of SEI film in the electrochemical reaction of the sodium ion battery, thereby further improving the first coulombic efficiency of the sodium ion battery.

[0020] Preferably, the preparation process of the positive electrode sheet is specifically as follows: A NaFePO4-CuFePO4 composite material, a conductive agent and a carboxymethyl cellulose binder in a weight ratio of (78-82):(8-12):(8-12), wherein the weight ratio of NaFePO4 and CuFePO4 in the NaFePO4-CuFePO4 composite material is (75-85):(15-25), are evenly mixed, and then dispersed in a solvent, wet-milled and mixed, and then coated on a metal aluminum foil, and after drying, curing and compacting, a positive electrode sheet is obtained.

[0021] Through the above technical scheme, the present application adopts a layered transition metal phosphate NaFePO4-CuFePO4 composite material with high sodium storage capacity and structural stability as the active material of the positive electrode, and limits the ratio between NaFePO4 and CuFePO4 in the NaFePO4-CuFePO4 composite material, so that the two can fully exert their synergistic effect, so that the positive electrode material has higher cycle stability and sodium storage capacity.

[0022] Preferably, Mn element is also added to the NaFePO4-CuFePO4 composite material, and the content of Mn element accounts for 1-5% of the mass of the entire composite material.

[0023] Through the above technical scheme, the present application further adds the Mn element to the NaFePO4-CuFePO4 composite material, which can further improve the electronic conductivity and thermal stability of the negative electrode material, thereby further improving the power density and operating temperature range of the sodium ion battery, so that the sodium ion battery has excellent electrochemical properties.

[0024] Preferably, the electrolyte is 1 mol / L NaPF6, the volume ratio of EC and DMC is 1:1, and a mixed solution of FEC-VC is added at 0.5-1.5% of the total volume of the electrolyte.

[0025] Through the above technical scheme, the present application selects EC (ethylene carbonate)-DMC (dimethyl carbonate) mixed solvent containing sodium salt as the electrolyte, and adds 0.5-1.5% FEC (fluoroethylene carbonate)-VC (vinylene carbonate) of the total volume of the electrolyte thereto, wherein the volume ratio of FEC and VC is 1:1, which gives full play to the synergistic effect of FEC and VC, so that the electrolyte can form a more stable SEI film on the electrode surface, significantly improves the stability of the electrolyte, and enhances the electrochemical performance of the sodium ion battery.

[0026] In summary, this application has the following beneficial technical effects: 1. The production process of this application optimizes the negative electrode active material of the sodium ion battery, which not only improves the electrochemical performance of the sodium ion battery, but also reduces the preparation cost of the negative electrode material, and broadens the development space of the sodium ion battery; 2. The production process of the present application selects a more suitable negative electrode binder, which can inhibit the excessive generation of SEI film in the electrochemical reaction, reduce the consumption of sodium ions, and improve the first coulombic efficiency of sodium ion batteries; 3. The production process of the present application optimizes the positive electrode active material of the sodium ion battery, so that the sodium ion battery has higher cycle stability and sodium storage capacity, and enhances the electrochemical performance of the sodium ion battery; 4. The production process of the present application optimizes the electrolyte of the sodium ion battery, so that the electrolyte can form a more stable SEI film on the electrode surface, significantly improving the stability of the electrolyte and enhancing the electrochemical performance of the sodium ion battery. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0028] Unless otherwise specified, the raw materials used in this application are all commercially available products.

[0029] The diaphragm of the present application adopts the diaphragm commonly used in the art. In the specific embodiment of the present application, pure glass fiber filter paper Whatman GFD (thickness of 675 μm) is used as an example for description; The specification of the metal aluminum foil in this application is (12±2)μm×528mm, and the reference surface density is 3.4mg / cm 2 ; The graphene oxide of the present application is prepared by the Hummer method, has an effective component content of 99%, and a diameter range of 0.5-3 μm; The asphalt of the present application has a flash point of ≥230°C, a softening point of 100-110°, an ash content of ≤2%, a needle penetration of 15-25, a solubility of ≥98%, and a ductility of ≥8%; The conductive agents in the positive electrode sheet and the negative electrode sheet of the present application are all commonly used conductive agents in the art. In the specific implementation of the present application, conductive carbon black is used as an example for illustration. The conductive carbon black particles of the present application have a diameter of 23 nm and a nitrogen attachment specific surface area of ​​220 m 2 / g, DBP absorption is 140cm 3 / 100g, volatile content is 1.4%, pH value is 6.4, ash content is 0.2%; The solvents in the positive electrode sheet and the negative electrode sheet of the present application are all commonly used solvents in the art. In the specific implementation of the present application, N-methylpyrrolidone is used as an example for illustration; The carboxymethyl cellulose binder of the present application is a mixture of carboxymethyl cellulose and styrene-butadiene rubber in a weight ratio of 1:1; The NaFePO4-CuFePO4 composite material of the present application is a Cu-doped sodium iron phosphate, and its preparation method is a common preparation method in the art, specifically, iron source, sodium source, phosphorus source and copper source are mixed uniformly according to a certain ratio, added to deionized water and stirred for dissolution, and then the pH value is adjusted to an alkaline condition, aged at a temperature of 80 ° C for 24 hours, and the obtained precipitate is washed and dried, and calcined under the protection of an inert gas to obtain a NaFePO4-CuFePO4 composite material having a weight ratio of (75-85) to (15-25) of NaFePO4 and CuFePO4. When it is necessary to add Mn element thereto, the manganese source is mixed uniformly with components such as the iron source.

[0030] The FEC-VC of the present application is prepared by mixing FEC and VC in a volume ratio of 1:1.

[0031] Preparation Example 1 Sulfurized asphalt is prepared by the following method: 500 g of asphalt and 900 g of sublimated sulfur were mixed evenly and loaded into a sealed kettle, and then treated at 250° C. for 3.0 hours under the protection of Ar gas to obtain sulfided asphalt.

[0032] Preparation Example 2 Sulfurized asphalt is prepared by the following method: 500 g of asphalt and 1100 g of sublimated sulfur were mixed evenly and loaded into a sealed kettle, and then treated at 300° C. for 2.5 hours under the protection of Ar gas to obtain sulfided asphalt.

[0033] Example 1 A production process for a sodium ion battery comprises the following steps: S1. Preparation of positive electrode 78g of NaFePO4-CuFePO4 composite material, 10g of conductive carbon black and 12g of carboxymethyl cellulose binder were mixed evenly, wherein the weight ratio of NaFePO4 to CuFePO4 in the NaFePO4-CuFePO4 composite material was 75:25, and then dispersed in N-methylpyrrolidone, wet ball milled and mixed, and then coated on a metal aluminum foil by spin coating, dried at 110°C for 12h under vacuum conditions, and then compacted at a pressure of 16MPa to obtain a positive electrode sheet, wherein the single surface density of the positive electrode sheet is 20mg / cm 2 , double-sided surface density is 40mg / cm 2 ; S2. Preparation of negative electrode sheet a. Disperse 10 g of graphene oxide in water, then add 120 g of amylopectin and stir at 80 ° C for 3.0 hours, then cool to 35 ° C, add asphalt dispersed in anhydrous ethanol and stir for 20 minutes to obtain a mixed solution, the amount of asphalt is 300 g; spray freeze-dry the mixed solution, and then carbonize it at 950 ° C for 3.5 hours under Ar gas protection to obtain an active material; b. 75 g of active material, 10 g of conductive carbon black and 15 g of sodium alginate were mixed evenly, then dispersed in N-methylpyrrolidone, magnetically stirred evenly, and then coated on a metal aluminum foil by spin coating, and then dried at 110°C for 12 h under vacuum conditions, and then compacted at a pressure of 16 MPa to obtain a negative electrode sheet, wherein the single surface density of the negative electrode sheet is 20 mg / cm 2 , double-sided surface density is 40mg / cm 2 ; S3. Assembly of sodium-ion batteries The positive and negative electrodes are wound, flattened, welded to the current collector, and then encapsulated, shelled, spot-bottom welded, grooved, and baked to make the moisture content of the positive electrode ≤100ppm and the moisture content of the negative electrode ≤150ppm. Then the electrolyte is injected. The battery surface temperature is ≤35°C before injection. The electrolyte specification is 1 mol / L NaPF6, the volume ratio of EC and DMC is 1:1, and a mixed solution of FEC-VC with a total volume of 0.5% of the electrolyte is added. The injection volume is 45g. After the injection is completed, the cap is laser welded, sealed, cleaned, oiled, and coated, and then left to stand at 25°C for 48 hours. After formation, aging, and capacity separation, the sodium ion battery is assembled.

[0034] Example 2 A production process for a sodium ion battery comprises the following steps: S1. Preparation of positive electrode 80g of NaFePO4-CuFePO4 composite material, 12g of conductive carbon black and 8g of carboxymethyl cellulose binder were mixed evenly, wherein the weight ratio of NaFePO4 to CuFePO4 in the NaFePO4-CuFePO4 composite material was 80:20, and then dispersed in N-methylpyrrolidone, wet ball milled and mixed, and then coated on a metal aluminum foil by spin coating, dried at 110°C for 12h under vacuum conditions, and then compacted at a pressure of 16MPa to obtain a positive electrode sheet, wherein the single surface density of the positive electrode sheet is 20mg / cm 2 , double-sided surface density is 40mg / cm 2 ; S2. Preparation of negative electrode sheet a. Disperse 10 g of graphene oxide in water, then add 140 g of amylopectin and stir at 82 ° C for 2.8 hours, then cool to 38 ° C, add asphalt dispersed in anhydrous ethanol and stir for 25 minutes to obtain a mixed solution, the amount of asphalt is 420 g; spray freeze-dry the mixed solution, and then carbonize it at 1000 ° C for 3 hours under Ar gas protection to obtain an active material; b. 80 g of active material, 15 g of conductive carbon black and 5 g of sodium polyacrylate were mixed evenly, then dispersed in N-methylpyrrolidone, magnetically stirred evenly, and then coated on a metal aluminum foil by spin coating, and then dried at 110°C for 12 h under vacuum conditions, and then compacted at a pressure of 16 MPa to obtain a negative electrode sheet, wherein the single surface density of the negative electrode sheet is 20 mg / cm 2 , double-sided surface density is 40mg / cm 2 ; S3. Assembly of sodium-ion batteries The positive and negative electrodes are wound, flattened, welded to the current collector, and then encapsulated, shelled, spot-bottom welded, grooved, and baked to make the moisture content of the positive electrode ≤100ppm and the moisture content of the negative electrode ≤150ppm. Then the electrolyte is injected. The battery surface temperature is ≤35°C before injection. The electrolyte specification is 1 mol / L NaPF6, the volume ratio of EC and DMC is 1:1, and a mixed solution of FEC-VC with a total volume of 1% of the electrolyte is added. The injection volume is 45g. After the injection is completed, the cap is laser welded, sealed, cleaned, oiled, and coated, and then left to stand at 25°C for 48 hours. After formation, aging, and capacity separation, the sodium ion battery is assembled.

[0035] Example 3 A production process for a sodium ion battery comprises the following steps: S1. Preparation of positive electrode 82g of NaFePO4-CuFePO4 composite material, 8g of conductive carbon black and 10g of carboxymethyl cellulose binder were mixed evenly, wherein the weight ratio of NaFePO4 to CuFePO4 in the NaFePO4-CuFePO4 composite material was 85:15, and then dispersed in N-methylpyrrolidone, wet ball milled and mixed, and then coated on a metal aluminum foil by spin coating, dried at 110°C for 12h under vacuum conditions, and then compacted at a pressure of 16MPa to obtain a positive electrode sheet, wherein the single surface density of the positive electrode sheet is 20mg / cm 2 , double-sided surface density is 40mg / cm 2 ; S2. Preparation of negative electrode sheet a. Disperse 10 g of graphene oxide in water, then add 160 g of amylopectin and stir at 85 ° C for 2.5 hours, then cool to 40 ° C, add asphalt dispersed in anhydrous ethanol and stir for 30 minutes to obtain a mixed solution, the amount of asphalt is 560 g; spray freeze-dry the mixed solution, and then carbonize it at 1050 ° C for 2.5 hours under Ar gas protection to obtain an active material; b. 85 g of active material, 5 g of conductive carbon black and 10 g of carboxymethyl cellulose binder were mixed evenly, then dispersed in N-methylpyrrolidone, magnetically stirred evenly, and then coated on a metal aluminum foil by spin coating, and then dried at 110°C for 12 h under vacuum conditions, and then compacted at a pressure of 16 MPa to obtain a negative electrode sheet, wherein the single surface density of the negative electrode sheet is 20 mg / cm 2 , double-sided surface density is 40mg / cm 2 ; S3. Assembly of sodium-ion batteries The positive and negative electrodes are wound, flattened, welded to the current collector, and then encapsulated, shelled, spot-bottom welded, grooved, and baked to make the moisture content of the positive electrode ≤100ppm and the moisture content of the negative electrode ≤150ppm. Then the electrolyte is injected. The battery surface temperature is ≤35°C before injection. The electrolyte specification is 1 mol / L NaPF6, the volume ratio of EC and DMC is 1:1, and a mixed solution of FEC-VC with a total volume of 1.5% of the electrolyte is added. The injection volume is 45g. After the injection is completed, the cap is laser welded, sealed, cleaned, oiled, and coated, and then left to stand at 25°C for 48 hours. After formation, aging, and capacity separation, the sodium ion battery is assembled.

[0036] Example 4 A production process of a sodium ion battery, which is different from that of Example 2 in that: in step a of step S2, corn starch (branched chain content is 80%) is used as starch, and the rest is the same as that of Example 2.

[0037] Example 5 A production process for a sodium ion battery, which is different from that of Example 2 in that: in step a of step S2, starch is high-branched starch (branched content is 40%), and the rest is the same as that of Example 2.

[0038] Example 6 A production process for a sodium ion battery, which is different from that of Example 2 in that: in step a of step S2, the asphalt is the sulfide asphalt obtained in Preparation Example 1, and the rest is the same as that of Example 2.

[0039] Example 7 A production process for sodium ion batteries, which is different from Example 2 in that: in step a of step S2, the asphalt is the sulfide asphalt obtained in Preparation Example 2, and the rest is the same as Example 2.

[0040] Example 8 A production process for a sodium ion battery, which differs from that of Example 2 in that: 5g of sodium polyacrylate in step b of step S2 is replaced with sodium alginate and sodium polyacrylate in a weight ratio of 0.8:1, wherein the sodium alginate is 2.22g and the sodium polyacrylate is 2.78g, and the rest is the same as in Example 2.

[0041] Example 9 A production process for a sodium ion battery, which is different from that of Example 2 in that: 5g of sodium polyacrylate in step b of step S2 is replaced with sodium alginate and sodium polyacrylate in a weight ratio of 1:1, wherein the sodium alginate is 2.5g and the sodium polyacrylate is 2.5g, and the rest is the same as in Example 2.

[0042] Example 10 A production process for a sodium ion battery, which differs from that of Example 2 in that 5 g of sodium polyacrylate in step b of step S2 is replaced with sodium alginate and sodium polyacrylate in a weight ratio of 1.2:1, wherein the sodium alginate is 2.73 g and the sodium polyacrylate is 2.27 g, and the rest is the same as in Example 2.

[0043] Embodiment 11 A production process for a sodium ion battery, which is different from that of Example 2 in that: 5g of sodium polyacrylate in step b of step S2 is replaced with sodium polyacrylate and carboxymethyl cellulose binder in a weight ratio of 1:1, wherein the sodium polyacrylate is 2.5g and the carboxymethyl cellulose binder is 2.5g, and the rest is the same as Example 2.

[0044] Example 12 A production process for a sodium ion battery, which is different from that of Example 2 in that: 5g of sodium polyacrylate in step b of step S2 is replaced with sodium alginate and carboxymethyl cellulose binder in a weight ratio of 1:1, wherein the sodium alginate is 2.5g and the carboxymethyl cellulose binder is 2.5g, and the rest is the same as Example 2.

[0045] Embodiment 13 A production process for a sodium ion battery, which is different from that of Example 2 in that 5g of sodium polyacrylate in step b of step S2 is replaced with sodium alginate, and the rest is the same as that of Example 2.

[0046] Embodiment 14 A production process for a sodium ion battery, which differs from Example 2 in that the NaFePO4-CuFePO4 composite material in step S1 is replaced by NaMnPO4-NaFePO4-CuFePO4, wherein the content of Mn accounts for 1% of the mass of the entire composite material, and the rest is the same as Example 2.

[0047] Embodiment 15 A production process for a sodium ion battery, which differs from Example 2 in that the NaFePO4-CuFePO4 composite material in step S1 is replaced by NaMnPO4-NaFePO4-CuFePO4, wherein the content of Mn accounts for 5% of the mass of the entire composite material, and the rest is the same as Example 2.

[0048] Comparative Example 1 The difference from Example 2 is that: in step a of step S2, no asphalt is added, and the solution obtained by mixing 40 g of graphene oxide and 560 g of starch is directly spray-freeze-dried, and the rest is the same as Example 2.

[0049] Comparative Example 2 The difference from Example 2 is that: in step a of step S2, graphene oxide is not added, and the mixture of 150g starch and 450g asphalt is directly spray-freeze-dried, and the rest is the same as Example 2.

[0050] Comparative Example 3 The difference from Example 2 is that 5 g of sodium polyacrylate in step b of step S2 is replaced by 5 g of polyvinylidene fluoride, and the rest is the same as Example 2.

[0051] Comparative Example 4 The difference from Example 2 is that the NaFePO4-CuFePO4 composite material in step S1 is replaced by NaFePO4, and the rest is the same as Example 2.

[0052] Comparative Example 5 The difference from Example 2 is that FEC-VC is not added to the electrolyte in step S3, and the rest is the same as Example 2.

[0053] Comparative Example 6 The difference from Example 2 is that only 1% of the total volume of the electrolyte is added to the electrolyte in step S3, and the rest is the same as Example 2.

[0054] Comparative Example 7 The difference from Example 2 is that only 1% of the total volume of VC is added to the electrolyte in step S3, and the rest is the same as Example 2.

[0055] Performance Testing At room temperature, the electrochemical performance of the sodium ion batteries prepared in the above embodiments and comparative examples was tested, specifically: (1) in the voltage test range of 2.0-4.2V, the specific capacity of the sodium ion battery at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 10C (1C = 180mA / g) was tested in sequence, and then the current density was reduced to 0.1C to test its specific capacity, and the specific capacity corresponding to 0.1C, the specific capacity corresponding to 10C and the specific capacity when returning to 0.1C were recorded in Table 1; (2) under the conditions of a voltage test range of 2.0-4.2V and a current density of 0.4C, the battery was cycled for 100 cycles, and the capacity retention rate was recorded in Table 1.

[0056] Table 1 Performance test results Data Analysis: As can be seen from Table 1, the specific capacity of the sodium ion batteries prepared in Examples 1-3 of the present application at 0.1C is 281.73-285.42 mAh / g, and the specific capacity at 10C is 97.48-105.72 mAh / g, with a decrease rate of 62.96-65.50%. When the current density is reduced to 0.1C again, the specific capacity can be restored to 269.83-276.86 mAh / g, which is 3.0-4.5% lower than before, and after cycling it at 0.4C for 100 times, its capacity retention rate is 93.1-93.5%. The experimental data show that the sodium ion batteries prepared in Examples 1-3 of the present application have better charge and discharge performance, rate performance and cycle stability.

[0057] The difference between Example 4-5 and Example 2 is that starch with different branched chain contents is used. It can be seen from Table 1 that the specific capacity of Example 4-5 at 0.1C is 183.43-196.87mAh / g, and the specific capacity at 10C is 53.19-59.06mAh / g, with a decrease rate of 70-71%. When the current density is reduced to 0.1C again, the specific capacity can be restored to 171.52-185.06mAh / g, which is 6.0-6.5% lower than before, and after cycling it at 0.4C for 100 times, the capacity retention rate is 90.3-91.1%. All indicators are worse than those in Example 2. The experimental data show that the use of full-branched starch in this application can improve the charge and discharge performance, rate performance and cycle stability of sodium ion batteries.

[0058] The difference between Example 6-7 and Example 2 is that sulfided asphalt is used instead of ordinary asphalt. It can be seen from Table 1 that the specific capacity of Example 6-7 at 0.1C is 291.24-296.18 mAh / g, and the specific capacity at 10C is 131.06-148.09 mAh / g, with a decrease rate of 50-55%. When the current density is reduced to 0.1C again, the specific capacity can still be restored to 285.42-292.63 mAh / g, which is 1.2-2.0% lower than before, and after cycling it at 0.4C for 100 times, its capacity retention rate is 95.1-95.9%. All performance indicators are better than those of Example 2. The experimental data show that the further use of sulfided asphalt in Example 6-7 can improve the charge and discharge performance, rate performance and cycle stability of the sodium ion battery.

[0059] The difference between Example 8-10 and Example 2 is that a certain ratio of sodium polyacrylate and sodium alginate is mixed as the binder for the negative electrode. It can be seen from Table 1 that the specific capacity of Example 8-10 at 0.1C is 289.05-291.38 mAh / g, and the specific capacity at 10C is 121.40-125.29 mAh / g, with a decrease rate of 57-58%. When the current density is reduced to 0.1C again, the specific capacity can still be restored to 281.82-285.55 mAh / g, which is 2.0-2.5% lower than before, and after 100 cycles at 0.4C, the capacity retention rate is 94.2-94.5%, and all performances are better than Example 2. The experimental data show that Example 8-10 further uses a certain ratio of sodium polyacrylate and sodium alginate mixed as the binder for the negative electrode to further improve the charge and discharge performance, rate performance and cycle stability of the sodium ion battery.

[0060] The difference between Example 11-12 and Example 2 is that a certain ratio of sodium polyacrylate and carboxymethyl cellulose binder is mixed as the binder of the negative electrode, or a certain ratio of sodium alginate and carboxymethyl cellulose binder is mixed as the binder of the negative electrode. It can be seen from Table 1 that the specific capacity of Example 11-12 at 0.1C is 290.04-290.18 mAh / g, and the specific capacity at 10C is 116.02-116.07 mAh / g, with a decrease rate of 60%. When the current density is reduced to 0.1 again, the specific capacity of Example 11-12 is 290.04-290.18 mAh / g, and the specific capacity at 10C is 116.02-116.07 mAh / g, with a decrease rate of 60%. C, the specific capacity can still be restored to 283.66-283.80 mAh / g, which is 2.2% lower than before, and after 100 cycles at 0.4C, the capacity retention rate is 93.9-94.1%. Although the various performances are slightly higher than those in Example 2, the improvement effect is worse than that in Examples 8-10. The experimental data show that the use of a certain ratio of sodium polyacrylate and sodium alginate mixed as the binder for the negative electrode can give full play to the synergistic effect between the two, thereby improving the charge and discharge performance, rate performance and cycle stability of the sodium ion battery.

[0061] The difference between Example 13 and Example 2 is that sodium alginate is used instead of sodium polyacrylate as the binder for the negative electrode. It can be seen from Table 1 that the performance of Example 13 is slightly different from that of Example 2, and is lower than that of Examples 8-10. The experimental data once again shows that the use of a certain ratio of sodium polyacrylate and sodium alginate mixed as the binder for the negative electrode can further improve the charge and discharge performance, rate performance and cycle stability of the sodium ion battery.

[0062] The difference between Example 14-15 and Example 2 is that Mn element is further added to the positive electrode active material. It can be seen from Table 1 that the specific capacity of Example 14-15 at 0.1C is 293.66-296.24 mAh / g, and the specific capacity at 10C is 132.15-142.20 mAh / g, with a decrease rate of 52-55%. When the current density is reduced to 0.1C again, the specific capacity can still be restored to 288.37-291.80 mAh / g, which is 1.5-1.8% lower than before, and after 100 cycles at 0.4C, the capacity retention rate is 95.3-95.8%. The experimental data show that the further addition of Mn element to the positive electrode active material in Example 14-15 can further improve the charge and discharge performance, rate performance and cycle stability of the sodium ion battery.

[0063] The difference between Comparative Example 1-2 and Example 2 is that no asphalt or graphene oxide is added to the negative electrode active material. It can be seen from Table 1 that the specific capacity of Comparative Example 1-2 at 0.1C is 175.42-221.55mAh / g, and the specific capacity at 10C is 43.86-64.25mAh / g, with a decrease rate of 71-75%. When the current density is reduced to 0.1C again, the specific capacity can be restored to 163.14-208.26mAh / g, which is 6-7% lower than before, and after cycling it at 0.4C for 100 times, the capacity retention rate is 84.2-89.3%. All indicators are worse than those in Example 2. The experimental data show that the mixed use of starch, asphalt and graphene oxide in this application can significantly improve the charge and discharge performance, rate performance and cycle stability of sodium ion batteries.

[0064] The difference between Comparative Example 3 and Example 2 is that the binder used for the negative electrode is traditional polyvinylidene fluoride. It can be seen from Table 1 that the specific capacity of Comparative Example 3 at 0.1C is 274.88mAh / g, and the specific capacity at 10C is 87.97mAh / g, with a decrease rate of 68%. When the current density is reduced to 0.1C again, the specific capacity can be restored to 266.08mAh / g, which is 3.2% lower than before, and after cycling it at 0.4C for 100 times, its capacity retention rate is 85.2%. All indicators are worse than those in Example 2. The experimental data show that the use of traditional polyvinylidene fluoride will reduce the charge and discharge performance, rate performance and cycle stability of sodium ion batteries.

[0065] The difference between Comparative Example 4 and Example 2 is that only NaFePO4 is used as the positive electrode material. It can be seen from Table 1 that the specific capacity of Comparative Example 4 at 0.1C is 246.39 mAh / g, and the specific capacity at 10C is 76.38 mAh / g, with a decrease rate of 69%. When the current density is reduced to 0.1C again, the specific capacity can be restored to 236.53 mAh / g, which is 4% lower than before, and after cycling it at 0.4C for 100 times, its capacity retention rate is 84.7%. All indicators are worse than those in Example 2. The experimental data show that the use of NaFePO4-CuFePO4 composite material as the positive electrode active material in this application can further improve the charge and discharge performance, rate performance and cycle stability of sodium ion batteries compared with NaFePO4.

[0066] The difference between Comparative Examples 5-7 and Example 2 is that FEC-VC is not added to the electrolyte, or only one of FEC and VC is added. It can be seen from Table 1 that the specific capacity of Comparative Examples 5-7 at 0.1C is 275.12-280.44 mAh / g, and the specific capacity at 10C is 90.79-96.47 mAh / g, with a decrease rate of 65.6-67.0%. When the current density is reduced to 0.1C again, the specific capacity can be restored to 266.32-271.89 mAh / g, which is 3.0-3.2% lower than before, and after 100 cycles at 0.4C, the capacity retention rate is 85.1-88.9%, and all indicators are worse than those in Example 2. The experimental data show that the addition of FEC and VC to the electrolyte in the present application can give full play to the synergistic effect between the two, thereby further improving the charge and discharge performance, rate performance and cycle stability of the sodium ion battery.

[0067] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A production process for a sodium ion battery, comprising the following steps: The positive electrode sheet, the negative electrode sheet, the separator and the electrolyte are assembled to obtain a sodium ion battery, wherein the preparation method of the negative electrode sheet is specifically as follows: a. Dispersing graphene oxide in water, then adding starch and stirring at a temperature of 80-85°C for 2.5-3.0 hours, the weight ratio of starch to graphene oxide is (12-16):1, then cooling to 35-40°C, adding asphalt dispersed in anhydrous ethanol and stirring for 20-30 minutes to obtain a mixed solution, the weight ratio of asphalt to starch is (2.5-3.5):1; spray freeze drying the mixed solution, and then carbonizing it under the protection of inert gas to obtain an active material; b. The active material, conductive agent and binder are mixed evenly in a weight ratio of (75-85): (5-15): (5-15), and then dispersed in a solvent. After magnetic stirring, the mixture is coated on a metal aluminum foil, and then dried and pressed to obtain a negative electrode sheet.

2. A production process for a sodium ion battery according to claim 1, characterized in that: The starch in step a is amylopectin.

3. A production process for a sodium ion battery according to claim 1, characterized in that: The asphalt in step a is sulfided asphalt.

4. A production process for a sodium ion battery according to claim 3, characterized in that: The sulfided asphalt is prepared by the following method: Asphalt and sublimed sulfur in a weight ratio of 1:(1.8-2.2) are mixed evenly, and then treated at a temperature of 250-300°C for 2.5-3.0 hours under the protection of an inert gas to obtain sulfided asphalt.

5. The production process of a sodium ion battery according to claim 1, characterized in that: The carbonization treatment conditions in step a are: at a temperature of 950-1050° C. for 2.5-3.5 hours.

6. A production process for a sodium ion battery according to claim 1, characterized in that: The binder in step b is one of sodium alginate, sodium polyacrylate and carboxymethyl cellulose binders.

7. A production process for a sodium ion battery according to claim 6, characterized in that: The binder in step b comprises sodium alginate and sodium polyacrylate in a weight ratio of (0.8-1.2):

1.

8. The production process of a sodium ion battery according to claim 1, characterized in that: The preparation process of the positive electrode sheet is specifically as follows: A NaFePO4-CuFePO4 composite material, a conductive agent and a carboxymethyl cellulose binder in a weight ratio of (78-82): (8-12): (8-12) are mixed evenly, wherein the weight ratio of NaFePO4 and CuFePO4 in the NaFePO4-CuFePO4 composite material is (75-85): (15-25), and then dispersed in a solvent, wet ball milled and mixed, and then coated on a metal aluminum foil, and after drying, curing and compacting, a positive electrode sheet is obtained.

9. A production process for a sodium ion battery according to claim 8, characterized in that: Mn element is also added to the NaFePO4-CuFePO4 composite material, and the content of Mn element accounts for 1-5% of the mass of the entire composite material.

10. The production process of a sodium ion battery according to claim 1, characterized in that: The electrolyte is 1 mol / L NaPF6, the volume ratio of EC and DMC is 1:1, and a mixed solution of FEC-VC is added to the total volume of the electrolyte at 0.5-1.5%.